Analysis of River Capacity Rainfall on The Watershed in Village Galapuang Ulakan Region - Leilany, Lili; Arsyad, Nadra (Universitas Negeri Padang, 2024)
Natural phenomena that occur often cause disasters and losses for the community and cause some losses both from social, financial, education and so on. Therefore advances in the world of construction and technology in the scope of water here play a very important role in analyzing a disaster that occurs, one of which is flooding. Based on the method used in this research is descriptive quantitative where the analysis is carried out by modeling the cross-sectional capacity of the watershed using the help of HEC-RAS software with a case study of river capacity analysis for rainfall in the watershed in Nagari Kampuang Galapuang Ulakan with a river stem length of 19 km and an area of river 115 km² the analysis interview process was carried out directly to the local community affected by the incident and resulted in a conclusion explaining that the Batang Ulakan Watershed can reach its maximum discharge in just 2 hours 6 minutes 25 seconds. To achieve a peak discharge of 9.51 m³/s from its normal discharge. And during the 25 to 50 year planned rainfall return period, the cross-sectional capacity data found that the geological conditions which have elevations that are not much different between the river sections and residents' settlements have little difference, resulting in the Batang Ulakan Watershed section, Nagari, Galapuang Village, on average, overflowing as high as 0.447 m in each of the Batang Ulakan Region Watershed in the Galapuang Village